LEXICAL AND SEMANTIC VARIABILITY OF THE SPANISH LANGUAGE AS A PLOT CHARACTERISTIC IN MODERN CINEMA - Popova , Nataliia; Hryhorash, Daria (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article examines the role of lexical invariants found in Spanish-language feature films and television series produced in different countries. The article analyzes the impact of lexical and semantic variants of language units on the understanding and perception of plots by viewers. It is determined that the viewer's recognition of Spanish and Latin American equivalents, regional dialects, argot and jargon can broaden the intercultural framework of communication, deepen the knowledge of the historical, social, cultural and historical realities of a certain nation. Semantic differences in lexemes affect the plot of films, while lexicographic differences create unique images of characters in the viewers' minds. Metaphorical transfers and phraseology specific to a particular culture add deep axiological and cultural meaning to the plot. The authenticity and cultural context of Spanish-language films, reflected in the lexical and semantic features of the characters' speech, expand viewers’ communicative and linguistic competence in the modern globalized world. The aim of the study is to determine the role of lexical and semantic differences in the dialogues of Spanish-language films and to characterize their impact on their perception, creation of images and characters, as well as on the cultural exchange between Spanish-speaking countries and other cultures through the cinema. The study focuses on lexemes, phrases, metaphors, phraseological units and microtexts that differ in their lexicography or semantic content in Spanish and Latin American films. Semantic and contextual analysis of the linguistic material has been conducted to identify those differences. The methods used by the film industry to adapt films to their target audiences have also been identified. However, the comparison shows a simplification of the plot interpretation and a loss of regional authentic characteristics through the use of language adaptation. It has been found that interculturalism can contribute to the society globalization without losing cultural values through the inclusion of contextual explanations in film dialogues._______________References:• Kabre, T. Leksychni vidminnosti mizh ispans'koju movoju Pirenejs'kogo pivostrova ta ispans'koju movoju Ameryky: diahronichna perspektyva [Lexical differences between the Spanish of the Iberian Peninsula and the Spanish of the Americas: a diachronic perspective] (Kyiv, 2023).• Kabre, T. Ispans'ka mova v kino ta na telebachenni: kul'turna perspektyva [Spanish in cinema and television: a cultural perspective] (Kyiv, 2023).• Mel'nychuk, Ispans'ka mova: istorija, fonetyka, leksyka, gramatyka [Spanish language: history, phonetics, vocabulary, grammar] (Kyiv, 2022).• Shostak, Kul'turno-markovani slova v ispans'kij movi [Culturally Marked Words in Spanish] (Kyiv, 2020).• Bojko, Rol' aktora v stvorenni obraziv i dialogiv [The role of the actor in creating images and dialogues] (Kyiv, 2021).• Mel'nychuk, V. Mizhnarodnyj kinematograf [International Cinema] (Kyiv, 2022).
Keywords: lexical and semantic variation, Spanish language, cinema, contextual analysis, cultural connotation, language manipulation, metaphor, international communication